The Impact of Management Team Characteristics on Adoption Balanced Scorecard in Algerian Manufacturing Companies -The Contingency and The Upper Echelons Approach- - hellal, salim; tagraret, yazid (Journal of Research in Finance and Accounting, 2026)
This study aims to determine the impact of management team characteristics on adoption the balanced scorecard in Algerian manufacturing companies, where the study model was developed according to the assumptions of the Contingency theory as well as the Upper Echelons theory, the study included a sample of 28 Algerian manufacturing companies. The multiple regression analysis was used to analyze the questionnaire data and test the study hypotheses using the software SPSS v26. The study reached several results, the most important of which is that there is no statistically significant effect when it comes to educational level and age on the adoption of the Balanced Scorecard. There is, however, a negative impact of the tenure on the adoption of the balanced scorecard in Algerian manufacturing companies. The study recommends that decision-makers in Algerian companies should take into account the scientific foundations and assumptions when moving towards designing and adopting modern management methods, in order to improve the performance of their companies.